Food Choice And Preferences Among Libyan Residents In The Klang Valley, Malaysia - Abdalhadi Mohamed Masoud Mansour
This study emphasizes the importance of food as the basis of survival for every individual. Food choice and preference of different immigrant groups in various parts of the world have been known to be affected by various factors ranging from price and taste, to environment and acculturation. The choice of food has also been reported to have a different influence on the socio-cultural life in different parts of the world. Human migration from one place to another has been going on throughout human history. Libya is an Arab country in North Africa and its people are expected to exhibit Arab culture. Malaysia, on the other hand, is a South-east Asian country with a unique socio-cultural heritage that has attracted people from various parts of the world, Libya included. This research is aimed to determine the impact of food choice and preferences among Libyans resident in the Klang Valley in Malaysia on maintaining good health. A self-administered questionnaire of Libyan food choices and preferences and daily calorie intake as well as BMI were the variables employed to analyze the result of this study. From the result 252 questionnaires returned from 400 questionnaires distributed (63%) to Libyan residents in the Klang Valley in Malaysia. The mean value of the result of the descriptive statistics shows that Libyans who live in the Klang Valley prefer to eat Halal and environmentally friendly place, prefer energy diluted food as well as socialize and make friends. Also, the outcome of the multiple regression analysis shows that there is significant positive relationship between food choice and preferences and sociocultural background among Libyan residents in the Klang Valley in Malaysia. The study shows that the food choice p-value = (. 000 <0.05), which means that there is positive significant relationship between food choice and maintaining good health. Moreover, food preference outcomes signify that p-value = (. 000 <0.05) which means that there is positive significant relationship between food preferences and the maintenance of good health. Keywords: food choice, food preference, good health, food calorie and body Mass Index (BMI)